2008
DOI: 10.1111/j.1745-6584.2007.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Tracers to Evaluate Hydrogeologic Controls on River Salinization

Abstract: The salinization of rivers, as indicated by salinity increases in the downstream direction, is characteristic of arid and semiarid regions throughout the world. Historically, salinity increases have been attributed to various mechanisms, including (1) evaporation and concentration during reservoir storage, irrigation, and subsequent reuse; (2) displacement of shallow saline ground water during irrigation; (3) erosion and dissolution of natural deposits; and/or (4) inflow of deep saline and/or geothermal ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…In contrast, previous investigations of stream and land salinity problems across the globe typically report the groundwater as being circum-neutral to alkaline (Farber et al, 2004;Moore et al, 2008;Salama et al, 1999). Interaction of saline groundwater containing acidity with surface waterways and lakes at basin scales has not been previously investigated.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast, previous investigations of stream and land salinity problems across the globe typically report the groundwater as being circum-neutral to alkaline (Farber et al, 2004;Moore et al, 2008;Salama et al, 1999). Interaction of saline groundwater containing acidity with surface waterways and lakes at basin scales has not been previously investigated.…”
Section: Introductionmentioning
confidence: 59%
“…While acidity in saline groundwater is known to occur across southern Australia (Dickson and Giblin, 2009), the influence of this on surface waters was reported as being limited to primary saline lakes (Bowen and Benison, 2009) and some lakes salinised after land clearing (Shand and Degens, 2008). Furthermore, investigations of stream and land salinity problems associated with rising saline groundwater across the globe typically report the groundwater as being circum-neutral to alkaline (Farber et al, 2004;Moore et al, 2008;Salama et al, 1999). In contrast, we have found that rising saline ground water in inland parts of south-western Australia is carrying acidity that also results in increasing discharge of acidity (along with salt) to water-ways and wetlands.…”
Section: Discussionmentioning
confidence: 84%
“…While these low flow periods result in elevated Cl concentration, solute loads (the mass flux of solutes over a period of time) are significantly lower indicating salinity storage within the groundwater system. This particularly occurred during the 1950s drought when loads were less at El Paso than at Elephant Butte indicating salt storage likely within the shallow groundwater system as demonstrated by graph from Moore et al 2008. Conversely high flow periods have low concentrations with high loads.…”
Section: Rio Grande Salinity Sourcesmentioning
confidence: 99%
“…Conversely high flow periods have low concentrations with high loads. A final note on the historical solute record is that, irrespective of climate, the solute loads during the early part of the 1900s loads were higher (Bastien 2009), particularly in the lower portion of the basin (Moore et al 2008). This period of time coincides with EBID and the Middle Rio Grande Conservancy District (irrigation district near Albuquerque) began construction of the agricultural drains which potentially flushed 800 years worth of agricultural salt accumulation from the vadose zone and shallow groundwater.…”
Section: Rio Grande Salinity Sourcesmentioning
confidence: 99%
“…The negative economic impact of excessive salt v www.esajournals.org concentrations in the Rio Grande was recently estimated by the Rio Grande Project Salinity Management Coalition (RGPSMC, a group that brings together the Colorado, New Mexico, and Texas Rio Grande compact commissioners with interested federal, state, local, and university partners) at ; $11,000,000/year, with municipalities like El Paso, TX, shouldering the largest fractions of these costs (Michelsen et al 2009). In addition to the possible impact from agricultural sources, previous investigations have demonstrated that salt loads in the Rio Grande increase in part because of (1) the increasing annual temperatures southward which leads to higher evaporation and evapotranspiration rates in the irrigated fields, (2) the high geothermal gradient of the Rio Grande Rift, which may enhance upwelling of highly mineralized groundwater from deeper parts of basins, and (3) the dissolution of salt-rich sedimentary rocks in the central and southern parts of the Rio Grande Valley (Eastoe et al 2008, Phillips et al 2003, Hibbs and Merino 2006, Hogan et al 2007, Witcher et al 2004, Moore et al 2008. These complexities are highlighted in Fig.…”
Section: Social-ecological Contextmentioning
confidence: 99%